Curriculum Development Model: The Prospect of Schools Cultivating Language Skills of Early Childhood Students - Akmal Mundiri; Ayu Mayang Dini; Sarifah Sarifah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the curriculum development model used to develop language skills in early childhood at Namira Kraksaan Kindergarten. This study uses a qualitative approach with a case study type of research. This research is located at Namira Kindergarten, Kraksaan, Probolinggo. The technique of data collection was through 2 instruments, namely observation and interview, which were conducted with 4 informants (the principal, Deputy Head of Curriculum, and homeroom teacher for grades A and B). The data analysis technique uses the Interactive Model with data reduction activities, data presentation, and drawing conclusions. Data validity with source and technique triangulation process. The results showed that the model used by Namira Kraksaan Kindergarten in developing language and literacy curriculum for early childhood students was a grassroots model or a bottom-up approach. This development model takes several steps, namely need assessment, review of the curriculum used, identification of problems, democratic problem solving, curriculum planning and formulation of a new curriculum. Competence and indicators of achieving competence in the new curriculum are aimed at stimulating aspects of children's language development in accordance with the characteristics and demands of the times. Therefore, with the curriculum development model presented by the school, it shapes the language and literacy development of preschool children, which begins with the development of listening and speaking and then gradually leads to the development of children's literacy.